Prenatal screening of Down syndrome in assisted reproductive techniques pregnancies: A systematic review - Fatemeh Zahra Meamar; Mitra Savabi-Esfahani; Tahmineh Farajkhoda (International Journal of Reproductive BioMedicine)
Background: The interpretation of Down syndrome screening results in assisted reproductive technology (ART) pregnancies is challenging. Despite the high psychological burden that false positive results impose on parents, studies that have addressed interpretation of both serum and sonographic markers in both rounds of screening for Down syndrome diagnosis in post-ART pregnancies are limited.